2017
DOI: 10.21608/eajbsf.2017.17055
|View full text |Cite
|
Sign up to set email alerts
|

Larvicidal and Antifeedant Activities of Different Extracts from Leaves and Stems of Lantana camara (Verbenaceae) Against the Housefly, Musca domestica L.

Abstract: The journal of Toxicology and pest control is one of the series issued twice by the Egyptian Academic Journal of Biological Sciences, and is devoted to publication of original papers related to the interaction between insects and their environment. The goal of the journal is to advance the scientific understanding of mechanisms of toxicity. Emphasis will be placed on toxic effects observed at relevant exposures, which have direct impact on safety evaluation and risk assessment. The journal therefore welcomes p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The obtained results are agreed with Begum et al (2010) for the crude ethanolic leaves extracts of Calotropis procera and Anonna squamosal (LC 50 values were 282.5 and 550ppm), Begum et al, (2011) for ethanolic extracts of Calotropis procera (seeds) on 3 rd instar larvae of M. domestica (the 100.0% mortality was observed at 500ppm), Akhater et al (2012) for the fresh leaf of milk weed (Calotropise procera) juice against larvae of M. domestica, Sinthusiri et al (2013) for essential oils from Cinnamomum verum, Myristica fragrans and Syzygium aromaticum against M. domestica, Ogbalu et al (2014) for the aqueous leaf extract of tobacco (Nicotiana tabacum) on M. domestica Carapeto et al, (2017) for two formulations of Amanita muscaria against M. domestica with two methods of extraction, where the mean lethal concentration (LC 50 ) of aqueous extract from dried, powdered basidiomes (DPB) was approximately 1931.02ppm and the LC 50 for the fresh basidiomes liquefied in water (FLB) was about 30%. Also, similar results were recorded by Fouda et al (2017) for ethanolic, acetone and petroleum ether extracts of Lantana camara (leaves and stems) against 3 rd instar larvae of M. domestica, where petroleum ether extract from leaves and stems were more toxic than acetone and ethanolic one.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The obtained results are agreed with Begum et al (2010) for the crude ethanolic leaves extracts of Calotropis procera and Anonna squamosal (LC 50 values were 282.5 and 550ppm), Begum et al, (2011) for ethanolic extracts of Calotropis procera (seeds) on 3 rd instar larvae of M. domestica (the 100.0% mortality was observed at 500ppm), Akhater et al (2012) for the fresh leaf of milk weed (Calotropise procera) juice against larvae of M. domestica, Sinthusiri et al (2013) for essential oils from Cinnamomum verum, Myristica fragrans and Syzygium aromaticum against M. domestica, Ogbalu et al (2014) for the aqueous leaf extract of tobacco (Nicotiana tabacum) on M. domestica Carapeto et al, (2017) for two formulations of Amanita muscaria against M. domestica with two methods of extraction, where the mean lethal concentration (LC 50 ) of aqueous extract from dried, powdered basidiomes (DPB) was approximately 1931.02ppm and the LC 50 for the fresh basidiomes liquefied in water (FLB) was about 30%. Also, similar results were recorded by Fouda et al (2017) for ethanolic, acetone and petroleum ether extracts of Lantana camara (leaves and stems) against 3 rd instar larvae of M. domestica, where petroleum ether extract from leaves and stems were more toxic than acetone and ethanolic one.…”
Section: Discussionsupporting
confidence: 80%
“…This imposes a need for other alternative methods which are efficient, economic and environmentally safe. Botanical derivatives materialize as a possible larvicides, pupicides, oviposition deterrents, antifeedants and repellent agents against M. domestica adults (Fouda et al, 2017). The present study aimed at evaluating the potency of methanol, acetone, chloroform and petroleum ether extracts of Lagenaria siceraria leaves against 3 rd instar larvae of the housefly, Musca domestica (Diptera: Muscidae) a mechanical diseases vector.…”
Section: Introductionmentioning
confidence: 99%
“…These results were similar to Avila, 52 who found that lufenuron had a major impact on pupae due to the loss of a required quantity of water contents, 53 reduced the intensity of protein biosynthesis 54 and internal metabolic temperature increase resulting in reduced body fluid hindering proper sclerotization of the newly formed puparium leading to decreased pupal parameters that were studied during the experiment and agrees with the results obtained on M. domestica. 55 Lowest activity was observed in the case of flubendiamide where fecundity (81.56–99.44) and hatchability (80.00–99.60%) were higher. Weak chemosterilant activities of flubendiamide as compared to other IGRs have also been reported by Kong in armyworm.…”
Section: Discussionmentioning
confidence: 96%
“…Huge number of reported research works had focused on the botanical extracts of the indigenous plants of Egypt and their toxic effects on different insect species (e.g., Soliman and El-Sherif, 1995;Messeha, 1997;El-Kassas, 2001;Attiaa, 2002, Mohamed et al, 2003, Kamel et al 2005, Bakr et al, 2006, Mansour et al, 2011,El.-Maghraby etal. 2012,Al-Zarog and El-Bassiouny, 2013Elsiddig, 2015;Hosam et al, 2016;Abbas et al, 2017;Elhalawany and Dewidar, 2017;El-Rehawy, 2017, Khater, 2017Wahba et al, 2017;Fouda et al, 2017;Bakr and Abd El-Bar, 2017;Bakr et al, 2017Bakr et al, , 2018. In agreement with some of those reported results, the present study revealed differences in LC 50 and LC 95 values of the extracts of the nine tested plants species.…”
Section: Discussionmentioning
confidence: 99%